Performance evaluation of comprehensive bandwidth utilizationfor 10-gigabit passive optical network - N. A. Ismail; Sevia Mahdaliza Idrus; R. A. Butt; F. Iqbal; A. M. Zin; F. Atan (Bulletin of Electrical Engineering and Informatics, 2019)
Bandwidth allocation during upstream transmission is crucial to determine the efficiency and performance of a XG-PON. For XG-PON, bandwidth assignment is done based on T-CONT which represents a traffic class as per ITU recommendation. DBA scheme used in this paper is based on CBU to assign bandwidth to ONUs based on the T-CONT supporting QoS as per SLA. In this paper, CATV traffic is used as traffic generator which used for generation of Ethernet frames and results showed expected trend of mean upstream delay for traffic class T2, T3 and T4 as compared to recommended value which is below 1.5ms. These results prove that CBU can also be implemented on real time traffic.